بدائع الصنائع :منہج و اسلوب اور خصائص : “Badā’ʻ al-Ṣanā’ʻ: Methodology and Characteristics - Dr.Muhammad Usman; Talib Ali Awan (Al-Qamar, 2019)
This paper studies the methodology and characteristics of “Badā’ʻ al-Ṣanā’ʻ fĪ tartĪb al-Sharā’ʻ”, a manual of Ḥanafī school of Islamic Jurisprudence, written by renowned Ḥanafī Jurist ʻAlāʻ al-Ḍīn al-Kāsānī (d.587AH). It finds that the referred book deduces Islamic rulings using Quran, Ḥadīth, Ijmāʻ Qiyāṣ, analogical reasoning etc. The author mentions the opinions of different schools and then gives his findings on the under discussion issue. This book is different and unique in nature, argumentations and provisions. The study, comparing it with prominent other manuals of Fiqh, explains the distinctive features which give it an extraordinary status in jurisprudential literature?